2001
DOI: 10.1038/sj.ejcn.1601245
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol drinking and risk of non-Hodgkin's lymphoma

Abstract: Objective: To analyse the relation between alcohol intake and the risk of non-Hodgkin's lymphoma (NHL). Design: Hospital-based case -control study. Settings: The greater Milan area and the province of Pordenone, Northern Italy. Subjects: Cases were 446 (256 men and 190 women) with histologically confirmed incident NHL, and controls were 1295 (791 men and 504 women) with acute non-neoplastic conditions. Results: Compared to non-drinkers, the odds ratio (OR) was 0.92 for < 3 drinks per day, 0.98 for 3 -6 drinks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 16 publications
1
8
2
Order By: Relevance
“…14,16,19,30,38,40,42,43,55 Our results were also in accordance with the Interlymph findings in so far as in the pooled analysis no protective effect of alcohol was observed for European centers. 47 Similarly, the findings of the 2 other studies reporting an inverse association between alcohol intake and development of overall NHL were not based on European study populations, as one was a case-control study carried out in Japan 24 and the other one was a large American cohort study.…”
Section: Discussionsupporting
confidence: 81%
“…14,16,19,30,38,40,42,43,55 Our results were also in accordance with the Interlymph findings in so far as in the pooled analysis no protective effect of alcohol was observed for European centers. 47 Similarly, the findings of the 2 other studies reporting an inverse association between alcohol intake and development of overall NHL were not based on European study populations, as one was a case-control study carried out in Japan 24 and the other one was a large American cohort study.…”
Section: Discussionsupporting
confidence: 81%
“…18 At hospital admission, these patients were enrolled as cases in a case-control study conducted by the same Institution with the aim of providing information on the role of some sociodemographic factors, tobacco smoking, alcohol drinking, food consumption and risk of NHL. 3,11,19 All study participants signed an informed consent, according to the recommendations of the Ethical Committee. All subjects were interviewed by trained interviewers, using structured questionnaires, which included information on age, education, other socioeconomic factors, a problem-oriented medical history, dietary, drinking and smoking habits.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies 4,7,8 have suggested that alcohol consumption reduces the risk of NHL whereas others have found increased NHL risks among alcohol drinkers 9,10 or no relationships. 5,11 Whether tobacco smoking and alcohol drinking influence the prognosis of patients with lymphomas is still unclear. To our knowledge, only a recent population-based prospective study conducted in Italy 12 investigated the issue.…”
Section: Introductionmentioning
confidence: 99%
“…368,369,373,374,376,382,388,[394][395][396][397][398][399] In a recent pooled analysis of 9 case-control studies, Morton et al 398 reported a significant inverse association with alcohol (pooled OR 5 0.83, 95% CI: 0.76-0.89), which did not vary with frequency or duration of intake, or by type of alcoholic beverage (OR for beer only, compared to nondrinkers 5 0.85, 95% CI: 0.76-0.95; OR for wine only 5 0.85, 95% CI: 0.74-0.99; OR for liquor only 5 0.90, 95% CI: 0.74-1.09). In a subgroup analysis of 4 of the studies with sufficient data, relative risk estimates were lower for current drinkers (pooled OR 5 0.73, 95% CI: 0.64-0.84) than for former drinkers (pooled OR 5 0.95, 95% CI: 0.80-1.14), compared to nondrinkers.…”
Section: Lifestyle and Personal Factors Tobacco And Alcohol Usementioning
confidence: 99%